Periplogenin Activates ROS-ER Stress Pathway to Trigger Apoptosis via BIP-eIF2α- CHOP and IRE1α-ASK1-JNK Signaling Routes - Yang, Yingjuan; Liu, Yana; Zhang, Yanhua; Ji, Wei; Wang, Lan; Lee, Shao C. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Periplogenin (PPG), a natural compound isolated from traditional Chinese herb Cortex Periplocae, has been reported to possess anti-inflammatory and anti-cancer properties. Objective: The present study aims to investigate the antitumor effects of PPG and the underlying mechanism in human colorectal cancer cells. Methods: The inhibition of cell growth in vitro was assessed by MTT assay. The induction of apoptosis and the ROS production induced by PPG was investigated by flow cytometry analysis. Western blotting was applied to measure the protein expression. Small interference RNA (siRNA) and a specific pharmacological inhibitor were used to knock down or inhibit the expression of related genes. Results: PPG was able to cause the production of ROS, inhibit the cancer cell growth and induce apoptosis. Nacetylcysteine was able to inhibit ROS production and apoptosis. PPG up-regulated the protein levels of BIP, peIF2α and CHOP as well as IRE1α and p-JNK, and down-regulated the protein level of p-ASK1, all of which were reversed by N-acetylcysteine. Importantly, knockdown of CHOP or JNK protein level attenuated the PPGelicited apoptosis. Conclusion: PPG-induced apoptosis was regulated by ROS-mediated BIP/eIF2α/CHOP and BIP/ASK1/JNK signaling pathways in colon cancer cells, suggesting that PPG is a promising therapeutic agent for the treatment of human colon cancer.
Keywords: apoptosis